Comparison of virtual and physical dimensions in AM resin dental devices and fit of devices with conventionally produced base plates. Issue 1 (2nd January 2018) - Al Mortadi, Noor Abdullah; Eggbeer, Dominic; Lewis, Jeffrey; Williams, Robert
Abstract : Purpose: The purpose of this study is to develop and apply clinically relevant methods of analysing the accuracy of dental appliances fabricated using additive manufacture (AM) compared to the computer-aided design (CAD) geometry. The study also compared fit between conventionally laboratory-fabricated and AM-produced base plates. Design/methodology/approach: The techniques were applied to two types of dental devices where AM fabrication methods could foreseeably be used as an alternative to laboratory production. "L" and cubic shapes of defined dimensions and spatial locations were positioned on the devices which were fabricated using AM. For assessing the dimensions, the "L" and cubic shapes were then measured on the physical builds ten times and compared to the CAD model. To assess the fit of AM and lab-produced devices, three upper and three lower conventionally fabricated acrylic base plates were compared to three upper and three lower plates. Silicone impression material was allowed to set between the casts and the base plates which filled any discrepancy between the two surfaces. The thickness of this silicone media was measured ten times at five different points on each base plate type and the results compared. Findings: The results indicated that the evaluated CAD/AM technique is able to produce dental appliance components that are consistent with tolerance levels that would be expected with conventional methods of baseplate design. This research demonstrated that a fully CAD/AM methodology represents a potentially viable alternative to conventional lab-based methods for two types of dental appliances. Originality/value: This work is original. The authors do not believe any previous papers similar to the one submitted have been published.